Antecedents of burnout and its relationship to internal audit quality - Al Shbail, Mohannad; Salleh, Zalailah; Mohd Nor, Mohd Nazli (Business and economic horizons, 2018)
This paper presents an assessment on the effect and consequences of burnout as a factor impacting premature sign-offs (PMSO) among internal auditors. Hence, questionnaires were sent to 187 internal auditors from Jordan to gather data. The data analysis results show the presence of some job burnout antecedents which are: ethical tension, role conflict, role ambiguity, and neuroticism personality trait. For internal auditors, job burnout can reduce the level of their job satisfaction. Meanwhile, dissatisfaction in the workplace among internal auditors, may increase negative behaviours including premature sign-offs.